WORK-FAMILY CONFLICT WITH WORK STRESS MARRIED FEMALE LECTURER AT SATYA WACANA CHRISTIAN UNIVERSITY - Anastasya Punu; Sutarto Wijono (International Journal Labs, 2022)
Background: The Corona Virus Disease 2019 (COVID-19) phenomenon has recently shaken all citizens of the world and has turned into a global pandemic. Objective: This study aims to determine the relationship between work-family conflict and work stress in female lecturers. Methods: The research method used in this study is a quantitative approach, with non-probability sampling techniques, especially purposive sampling. Results: There are two measuring instruments in this study, namely the first, the Job Stress Scale (Parker & Decotiis, 1984) which consists of two aspects, namely time stress and anxiety with cronbach's alpha = 0.97 . Second, the Work-Family Conflict Scale (Carlson, Kacmar, & Williams, 2000) developed based on aspects of Greenhaus & Beutell (1985) namely time-based conflict, strain-based conflict, and behavior-based conflict with cronbach's alpha = 0.85. The calculation results using the pearson product moment correlation technique with the value of the correlation coefficient r = 0.411; p<0.05. This shows that there is a significant positive relationship between work family conflict and the work stress of female lecturers at Satya Wacana Christian University. Conslusion: Based on the results of the analysis of research data that has been carried out, it can be concluded that there is a positive and significant relationship between work-family conflict and work stress of female lecturers at UKSW.